2018
DOI: 10.15252/emmm.201708799
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin rescues mitochondrial myopathy via coordinated activation of autophagy and lysosomal biogenesis

Abstract: The mTOR inhibitor rapamycin ameliorates the clinical and biochemical phenotype of mouse, worm, and cellular models of mitochondrial disease, via an unclear mechanism. Here, we show that prolonged rapamycin treatment improved motor endurance, corrected morphological abnormalities of muscle, and increased cytochrome c oxidase (COX) activity of a muscle‐specific Cox15 knockout mouse (Cox15 sm/sm). Rapamycin treatment restored autophagic flux, which was impaired in naïve Cox15 sm/sm muscle, and reduced the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 33 publications
3
82
0
1
Order By: Relevance
“…Current evidence supports the protective role of autophagy and mitophagy in MDs as well as in other neurodegenerative disorders associated with impairment of mitochondrial functions (Lightowlers et al , ; Viscomi et al , ; Civiletto et al , ). Since we showed that miR‐181a/b regulate mitophagy and autophagy in the eye, we tested whether the latter processes are implicated in the amelioration of the phenotype mediated by miR‐181a/b downregulation.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Current evidence supports the protective role of autophagy and mitophagy in MDs as well as in other neurodegenerative disorders associated with impairment of mitochondrial functions (Lightowlers et al , ; Viscomi et al , ; Civiletto et al , ). Since we showed that miR‐181a/b regulate mitophagy and autophagy in the eye, we tested whether the latter processes are implicated in the amelioration of the phenotype mediated by miR‐181a/b downregulation.…”
Section: Resultsmentioning
confidence: 68%
“…These data show that the downregulation of miR-181a/b ameliorates the phenotype in both MRC complex III and IV defective models, indicating that the protective effect of miR-181a/b silencing is gene-independent. Current evidence supports the protective role of autophagy and mitophagy in MDs as well as in other neurodegenerative disorders associated with impairment of mitochondrial functions (Lightowlers et al, 2015;Viscomi et al, 2015;Civiletto et al, 2018). Since we showed that miR-181a/b regulate mitophagy and autophagy in the eye, we tested whether the latter processes are implicated in the amelioration of the phenotype mediated by miR-181a/b downregulation.…”
Section: Mir-181a/b Inhibition Protects Neurons From Cell Death and Amentioning
confidence: 88%
See 2 more Smart Citations
“…Preclinical studies suggest that a potential therapeutic target of disease progression is the mammalian target of rapamycin (mTOR) pathway, a biological route fundamental for regulating cell metabolism and physiology [13]. In mice models of Leigh syndrome, treatment with rapamycin, an mTOR inhibitor, extended lifespan and reduced disease progression and severity [14]. Civiletto et al provided evidence that rapamycin induces improvements in mitochondrial function and ultrastructure, indicating powerful clearance of dysfunctional organelles via activation of autophagic flux in skeletal muscle.Mitochondria are highly dynamic organelles that continuously fuse, divide, and move, and mitochondrial function is controlled and maintained by these morphologic changes.…”
mentioning
confidence: 99%